High mechanical properties, thermal conductivity and solvent resistance in graphene oxide/styrene-butadiene rubber nanocomposites by engineering carboxylated acrylonitrile-butadiene rubber. (1st December 2017) - Liu, Pengzhang; Zhang, Xumin; Jia, Hongbing; Yin, Qing; Wang, Jingyi; Yin, Biao; Xu, Zhaodong
Abstract: In this paper, graphene oxide (GO) was modified with carboxylated acrylonitrile-butadiene rubber (xNBR) to synthesize the xNBR modified GO (xNBR-GO), which was adopted to reinforce styrene-butadiene rubber (SBR) nanocomposites through latex compounding method. The interaction between GO and xNBR was verified by Fourier transform infrared spectroscopy (FTIR) and Raman spectra. The dispersion of filler and morphology of xNBR-GO/SBR nanocomposites were characterized by X-ray diffraction (XRD) and scanning electron microscope (SEM). The mechanical properties, dynamic mechanical properties, thermal stability, thermal conductivity as well as solvent resistance of the xNBR-GO/SBR nanocomposites were also thoroughly studied. It was confirmed that xNBR could interact with GO through hydrogen bonding. The modification would improve the dispersion and reinforcement of filler. With the incorporation of 5 phr (parts per hundred rubber) filler, the tensile strength, tear strength and thermal conductivity of xNBR-GO/SBR nanocomposite were increased by 545%, 351% and 31.7%, respectively. In addition, the equilibrium solvent uptake was decreased by 31.8%, and the thermal stability was enhanced.